OPTIMASI PENGGUNAAN MEDIA SOSIAL OLEH MAHASISWA HUKUM EKONOMI SYARIAH: ANALISIS STRATEGI EFEKTIF PADA PLATFORM YOUTUBE - Fakhrudin; Fauzi, Unang; Effendi, Erus; Dity, Annisa (Jurnal komunikan, 2024)
This research aims to analyze effective strategies in optimizing the use of social media, especially on the YouTube platform, by students of Sharia Economic Law. The focus of the study is on students' efforts to utilize social media as a relevant and beneficial tool within the context of social media business from an Islamic perspective, while also identifying legal protection issues related to YouTube social media content. The qualitative research method involves strategy analysis through surveys, interviews, and observations of Sharia Economic Law students, particularly those who are content owners (youtubers) actively using YouTube as a platform for content uploads. The content produced by youtubers is acknowledged as copyright that needs protection. The obtained data is then analyzed to explore and document comprehensive aspects within the JABODETABEK region. The research findings provide profound insights into the optimization of social media usage by Sharia Economic Law students, revealing inadvertencies in mentioning and attributing specific parties disseminated in the public domain. This may lead to prohibited defamation in Islam and conflict with the ITE Law. Islam emphasizes the importance of conveying information truthfully and avoiding manipulation or exploitation of facts. Other findings indicate that the presence of hackers has an impact on the protection of YouTube by youtubers. The implications of this research can contribute to the development of innovative learning strategies and enrich the understanding of students regarding the implementation of Sharia Economic Law in the digital era.